Full-scale test on steel arch with unconventional strap under lateral and gravity loads. - Zavala, Carlos (2002)
A non conventional purlin with triangular section and cross diagonals is proposed to be used in Steel Arch Structures. For this purpose a full scale arch of 7 meters span with 6 meters purlins, was built in order to perform a loading test under extreme gravity loads and monotonic test underlateral load. To prove the interaction between the supporting arch and the purlins, incremental gravity load was applied over each element. Elastic deflection of 0.007 m for 931 N/m load was found which is under the demand of AISC-LRFD (L/360). Maximum deflection of 0,013 m for 1470N/m load was found at the end of the test. To prove how effective is the bolt connection between the purlin and the arch, a full scale test under lateral monotonic load applied at one extreme was performed, to simulate the extreme wind load over the structure. A 2254 N load produces 0,05 m of lateral displacement on the system. This value was almost the beginning of the non-linear behavior of the structural system.